Establishment and characterization of three gemcitabine-resistant human intrahepatic cholangiocarcinoma cell lines - Jiandong Li; Yanxin Hu; Jiayao Zhang; Weiguang Zhang; Jianhua Yu; Baochun Lu (Scientific Reports)
Abstract Intrahepatic cholangiocarcinoma (ICC) is a highly malignant liver tumor associated with a dismal prognosis, largely due to chemotherapy resistance. However, the mechanisms underlying gemcitabine (GEM) resistance in ICC remain poorly understood. In this study, we established three GEM-resistant cell models and evaluated their resistance by assessing cell proliferation, cell cycle arrest, and DNA damage. GEM-resistant cells exhibited significant tolerance to GEM-induced growth inhibition, reduced cell cycle arrest, and decreased DNA damage compared to parental cells. We then explored potential resistance mechanisms and found that pathways and targets such as epithelial-mesenchymal transition, PI3K/Akt, p53R2, and IGF-1R did not show a significant correlation with ICC resistance. Interestingly, our findings suggested that reactive oxygen species might promote GEM resistance in ICC. In conclusion, we characterized a GEM-resistant ICC model, which can be employed to investigate alternative resistance mechanisms and explore new treatment approaches.